Programme and abstracts from the 16th Nordic Conference on Reindeer and Reindeer Husbandry Research, 16-18 November 2010, Tromsö, Norway - Haugerud, Rolf Egil; Hatteng, Björn; Nystad Eskonsipo (Editors), Berit M. (Rangifer, 2010)
The conference was organized by the Nordic Council for Reindeer Husbandry Research (NOR) and the Centre for Sami Studies (SESAM), University of Tromsø. The 128 participants shared a well organized conference with 31 lectures and 19 posters at the University of Tromsø 16-18 November 2010.